2023
DOI: 10.1039/d2np00091a
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and development of botanical natural products and their analogues as therapeutics for ovarian cancer

Abstract: This review highlights botanical natural products with activity against ovarian cancer and key drug development considerations for their advancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…Geniposide has obvious advantages in the treatment of osteoporosis, such as high biological activity and multiple therapeutic mechanisms [ 127 , 129 ]. It is precisely based on these advantages of natural products that it has become the most common choice for the development of new drugs against osteoporosis [ 136 ]. Both clinical and basic experiments have shown that natural products have enormous to exert anti-osteoporosis effects.…”
Section: Discussionmentioning
confidence: 99%
“…Geniposide has obvious advantages in the treatment of osteoporosis, such as high biological activity and multiple therapeutic mechanisms [ 127 , 129 ]. It is precisely based on these advantages of natural products that it has become the most common choice for the development of new drugs against osteoporosis [ 136 ]. Both clinical and basic experiments have shown that natural products have enormous to exert anti-osteoporosis effects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent review provides a summary of the primary mechanisms of action through which natural products cause anti-ovarian cancer effects, including cytotoxic effects, damage due to reactive oxygen species (ROS), cell cycle arrest, induction of autophagic cell death, promotion of DNA damage response, etc. [ 29 ]. More details of the basis to investigate the efficacy of these natural products on POF can be found in our Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer, a predominant gynecologic tumor originating from the ovary, uterus, and related tissues, represents the acknowledged 'king of gynecological cancers' with the highest mortality, lowest cure rate, and greatest recurrence rate among its counterparts [1,2]. A survey conducted by the American Cancer Society forecasts nearly 20,000 fresh incidents of ovarian cancer are projected to occur in the United States in 2022, accompanied by over 12,000 fatalities [3].…”
Section: Introductionmentioning
confidence: 99%